The Covid-19 Pandemic, Islamic Religious Education Teacher Self-Efficacy, and Implementation of Distance Learning from Home - Mokh. Iman Firmansyah; Agus Fakhruddin; Aceng Kosasih; Neng Rina Rahmawati; Vena Dwi Oktaviani; Elia Anggraeni (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to explore and analyze the experience of PAI teachers in carrying out learning process during the pandemic which is focused on three things; emotional regulation in response to school closure policies, their efforts to identify student learning facilities, and the learning strategies they choose. A qualitative approach with the phenomenological method was chosen to obtain information on the learning experiences of Islamic Religious education teachers of six Junior High Schools in Bandung, West Java, which were explored through semi-structured interviews and documentation. The results of the study found that there was psychological involvement and varied responses of the subject to school closure policies. In such conditions, they display self-efficacy to ensure the continuity of learning by carefully identifying student learning facilities and communicating effectively. The process has an impact on the implementation of their chose, with three strategies of Distance Learning (PJJ) from home, namely online; synchronous-asynchronous and outside the network with the module system. This study concludes that teacher self-efficacy plays a very important role in responding to and choosing appropriate learning strategies and technologies in various circumstances to ensure the continuity of learning, and at the same time recommending the improvement of these essential competencies to the Ministry of Education and Culture of the Republic of Indonesia on a regular and programmed basis.